Schienenpersonenfernverkehr in Deutschland. Sollen weitere Neubaustrecken überhaupt noch realisiert werden? - Vieregg, Martin (Deutscher Verkehrs-Verl., 2004)
Im Schienenpersonenfernverkehr (SPFV) ist in den vergangenen zehn Jahren eine rückläufige Verkehrsentwicklung zu beobachten, obwohl enorme Investitionen in den Aus- und Neubau von Strecken getätigt wurden. Es stellt sich die Frage, ob weitere Investitionen in die Infrastruktur des SPFV in Deutschland überhaupt noch gerechtfertigt werden können. difu

In spite of the massive investment in new rail tracks and rolling stock, rail passenger traffic in Germany (SPFV) has witnessed a negative trend for years. The investment made in infrastructure projects so far - especially in new rail tracks - shows a high degree of inefficiency (low capacity, minimal reduction in journey times, extremely high costs of investment). Questions are raised about the relationship between the construction of new rail tracks and the decline in traffic demand, and whether any new tracks for ICE services should be built in view of the poor results achieved. The French operators TGV Sud-Est and TGV Nord can be quoted as examples to prove that a high volume of traffic can be generated and that it is possible to well. Difu achieve profits without having to resort to taxpayers' subsidies. In view of Germany's greater population density and higher traffic demand, the rail passenger sector in Germany ought to be able to operate profitably as well. difu
Keywords: Öffentlicher Verkehr; Schienenpersonenverkehr; Eisenbahn; Fernverkehr; Verkehrsentwicklung; Verkehrsinfrastruktur; Wirtschaftlichkeit; Neubaustrecke; Streckenausbau; Bahnstrecke